The Phenomenon of Social Media Addiction among Adolescents: Implications for Guidance and Counselling Services - Rahmadhina, Alifa S; Fadillah, Ega Nur (Jurnal Indonesia Sosial Teknologi, 2025)
Low self-confidence constitutes a significant psychological barrier impeding students' English language learning outcomes, particularly in speaking contexts. While digitally based guidance and counseling services have emerged as promising interventions for addressing psychological challenges, empirical evidence regarding their effectiveness in enhancing self-confidence specifically for English learning remains limited, particularly in Indonesian educational contexts. This study employed a mixed-methods design combining a quasi-experimental pretest-posttest control group approach with phenomenological inquiry. Seventy-eight secondary school students were randomly assigned to experimental (n=38) and control (n=40) groups. The experimental group received an 8-week digital counseling intervention comprising synchronous online sessions, asynchronous messaging support, psychoeducational modules, virtual peer support groups, and self-monitoring tools. Data were collected using the Self-Confidence in English Learning Scale (SCELS) and semi-structured interviews with 14 participants. Quantitative data were analyzed using mixed-design ANOVA, while qualitative data underwent thematic analysis. The analysis revealed a significant group × time interaction effect (F(1,76)=62.71, p<.001, η²p=.452), indicating substantially greater improvement in self-confidence in the experimental group (M=+24.26) than in the control group (M=+5.17). Significant effects were observed across all subscales, with Communicative Confidence showing the largest effect (η²p=.390). Qualitative findings identified enhanced accessibility, psychological safety, skill development, and peer support as key mechanisms underlying intervention effectiveness. Digital-based counseling services significantly enhance students' self-confidence in English learning through multiple mechanisms. These findings support the integration of digital counseling platforms into school guidance programs to address affective barriers in language education.